2015
DOI: 10.2217/fon.14.193
|View full text |Cite
|
Sign up to set email alerts
|

miR-214: a potential biomarker and therapeutic for different cancers

Abstract: miRNAs (miRs), or small approximately 22-nucleotide-long single-stranded noncoding RNA molecules, interact with 3' untranslated regions of target mRNAs, leading to inhibition of protein production. miR-214 is often dysregulated in various cancers, which governs both tumorigenic and tumor suppressive functions. This review focuses on the current knowledge of miR-214 switching in diverse forms of cancer either by its upregulation or downregulation and sheds light on the mechanism of its tumorigenic and suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 91 publications
0
54
0
Order By: Relevance
“…Previous studies have demonstrated the association of miR-214 with the resistance to chemotherapeutic agents in several types of cancers 27, 28 . A recent study showed the potential of miR-214 to overcome the resistance to tamoxifen and fulvestrant in estrogen receptor-positive breast cancer cells 44 , and miR-214 was reported to induce the resistance to cisplatin in human ovarian cancer cells via the PTEN/Akt pathway 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the association of miR-214 with the resistance to chemotherapeutic agents in several types of cancers 27, 28 . A recent study showed the potential of miR-214 to overcome the resistance to tamoxifen and fulvestrant in estrogen receptor-positive breast cancer cells 44 , and miR-214 was reported to induce the resistance to cisplatin in human ovarian cancer cells via the PTEN/Akt pathway 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In human ovarian cancer cells, miR-214 was found to induce cisplatin resistance primarily through targeting the PTEN/Akt pathway 29 , and in human lung cancer cell line HCC827, miR-214 was reported to regulate the acquired resistance to gefitinib via PTEN/AKT signaling pathway 30 . Taking previous reports together, miR-214 may be involved in the proliferation, cell cycle and apoptosis of cancer cells through directly mediating target PTEN, NECL2, FGFR, NRAS, beta-catenin, UBC9, EZH2 and P53 genes or indirectly regulating downstream signaling molecules 27, 28 . It is therefore hypothesized that miR-214 may mediate the resistance of EGFR-mutant NSCLC to TKIs through mediating cancer cell apoptosis-associated target genes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the current study, we aimed to exploit the potential contributions of miRNAs to the cytoprotection network in erythroid cells under external stress conditions. miR-214 has been demonstrated to modulate cell survival and apoptosis in other types of cells including cancer cells by directly targeting important cell survival-relevant genes [36,37]. A recent study also demonstrated that miR-214 directly targets ATF4 to restrain bone formation in osteoclasts by suppressing osteoclast activity [38].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-214 (miR-214) and microRNA-126 (miR-126) regulate angiogenesis, proliferation, migration, and cell death of cancer cells; and thus, dysregulation of these 2 miRNAs critically influences tumour progression 17, 18 . Furthermore, circulating miR-214 or -126 levels are increased in 6 human tumours (multiple myeloma 19 , osteosarcoma 20 , breast 21 , gastric 22 , ovarian 23 , and non-small cell lung carcinoma 24 ) and a canine sarcoma (canine hemangiosarcoma 25 ).…”
Section: Introductionmentioning
confidence: 99%